The effect of Laja in dyslipidemia: an interventional pre-post test - V. S., Renjumol; A. K., Sajeeshan; S., Sheela (International Journal Of Community Medicine And Public Health, 2024)
Background: Dyslipidemia is a lipoprotein metabolism disorder and a major risk factor for Cardio Vascular Diseases. The National Cholesterol Education Programme (NCEP) guidelines suggest dietary modifications, exercise and weight control as the main foundation of dyslipidemia treatment. Dyslipidemia can be considered as a kapha medoja vikara, managed with correction of agni and kaphamedahara drugs. Lāja (puffed rice) is an aharadravya ideal in this condition because it is having kaphamedahara property. Methods: This study was conducted at Govt. Ayurveda College, Tripunithura as an interventional pre-post study with control group to find out solution for normalizing lipid profile by changing diet without therapeutic medicine. 30 Participants were allotted in each groups by consecutive sampling and advised to follow diet restriction and exercise for both groups. In addition the study group consumed the Lāja peya two times daily before food. Study period was 90 days and assessment taken in 0th, 46th and 91st day. Results: The results showed significant effect on lipid profile in both groups. But in comparison to control group, the study group showed highly significant reduction in Total cholesterol, LDL, VLDL and Triglycerides and not in increasing HDL. Conclusions: Lāja which contains rice bran, low in fat and has Kashaya Madurarasa, lakhu alparooksha guna, agnideepana, kaphachidah and medahara property, that helps to digest the food properly and correct the metabolism. Thus laja peya has a beneficiary role in reducing Total cholesterol, LDL, VLDL and Triglycerides and there is no role in increasing HDL.